Synthesis, Antimicrobial Evaluation and Hemolytic Activity of 2-[[5-alkyl/aralkyl substituted-1,3,4-oxadiazol-2-yl]thio]-N-[4-(4-morpholinyl)phenyl]acetamide derivatives - Akhtar, Muhammad Nadeem; Gul, Samreen; Rehman, Aziz-ur; Abbasi, M. Athar; Khan, Khalid Mohammed; Nafeesa, Khadija; Siddiqa, Asia; Shahid, Muhammad; Subhani, Zinayyera (Elsevier, 2017)
2,5-Disubstituted 1,3,4-oxadiazole compounds are one of the most attractive classes for researchers due to their pharmacological activities. In the current research, a new series of 2-[[5-alkyl/aralkyl-1,3,4-oxadiazol-2-yl]thio]-N-[4-(4-morpholinyl)phenyl]acetamides (6a–m) were prepared by converting different aryl/aralkyl organic acids (1a–m) successively into corresponding esters (2a–m), hydrazides (3a–m) and 5-aryl/aralkyl-1,3,4-oxadiazol-2-thiols (4a–m). Finally, the target compounds 6a–m were synthesized by stirring 5-aryl/aralkyl-1,3,4-oxadiazol-2-thiols (4a–m) with 2-bromo-N-[4-(4-morpholinyl)phenyl]acetamide (5) in the presence of N,N-dimethylformamide (DMF) and sodium hydride (NaH). The structures of the synthesized compounds were elucidated through IR, 1H-NMR, 13C-NMR and mass spectral data. The compounds were also screened for antimicrobial and hemolytic activity and most of them were found to be active against the selected microbial species at variable extent relative to reference standards. The compounds, 6d and 6f were active against the selected panel of microbes and the former was the most potent one. This series showed less toxicity and may be considered for further biological screening and application trial except 6h and 6l, possessing higher cytotoxicity.